Soliton solutions of a generalized Hirota-Satsuma equation using Darboux transformation - mousa, rahma sadat (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
A modified version of the generalized Hirota-Satsuma equation is solved analytically using Darboux transformations (DT), we start with the Lax pair of this equation and apply DT. This leads to another solvable pair containing a new eigen functions that is a solution of the equation. Several seeds solutions are tested as well as one and two solitons forms are obtained using DT. A suitable choice of the seed fields leads to new solutions.